The effect of job flexibility on female labor market outcomes: estimates from a search and bargaining model - Flabbi, Luca; Moro, Andrea (Bonn, 2010)
"This paper develops and estimates a search model of the labor market where jobs are characterized by wages and work-hours flexibility. Flexibility is valued by workers, and is costly to provide for employers. The model generates observed wage distributions directly related to the preference for flexibility parameters: the higher the preference for flexibility, the wider is the support of the wage distribution at flexible jobs and the larger is the discontinuity between the wage distribution at flexible and non-flexible jobs. Estimation results show that more than one third of women place positive value to flexibility, with women with a college degree valuing flexibility more than women with a high school degree. Counterfactual experiments show that flexibility has a substantial impact on the wage distribution but not on the unemployment rate. We comment on the implications of our approach for gender differentials in wages and schooling."